PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SISWA BERPRESTASI DENGAN METODE SIMPLE ADDITIVE WEIGHTING (STUDI KASUS: SMK WIRABUANA 2) - Adinda Dwi Lestari; Febrian Irfan Syafiq; Saprudin (CV. Multi Kreasi Media, 2024)
The selection of high-achieving students at SMK Wirabuana 2 is currently based solely on report card grades and is done manually. The implementation of this decision support system can assist the school in selecting high-achieving students more accurately. A decision support system is a system that generates alternative decisions that can be used as a tool in decision-making. In this study, students are selected using the simple additive weighting (SAW) method. This method is chosen because it assigns weights to each criterion, followed by a ranking process that selects the best alternative from multiple options. The school has four criteria: average report card grades, attendance, extracurricular activities, and behavior. It is expected that this method will provide more accurate assessments, as it is based on predefined criteria and weights to yield more accurate results as a supporting tool.